2017
DOI: 10.1016/j.ijom.2017.02.282
|View full text |Cite
|
Sign up to set email alerts
|

Is the aetiology of facial trauma in Libya is the same as in the west?

Abstract: Background: Closure of facial lacerations in young children can be difficult under local anaesthetic (LA) in an emergency department (ED) setting. Sedation or general anaesthetic (GA) is often required to close lacerations safely and to a good surgical standard. Our hospital introduced local anaesthetic gel (LAT) in 2015 to reduce the need for paediatric admissions. Objectives: To ascertain the usefulness of LAT in reducing paediatric admissions. Methods: Data was collected prospectively of all children presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is also evidence that increased rates of violence within the social environment can be associated with aggressiveness and antisocial behaviour among children . This could be the case for war‐torn Libya, where assault and violence are increasingly recognized as a cause of facial injuries among Libya adults . Thus, it can be hypothesized that war and its related violence in Libya could have increased the risk of TDIs by increasing the antisocial behaviour and violent behaviour among children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that increased rates of violence within the social environment can be associated with aggressiveness and antisocial behaviour among children . This could be the case for war‐torn Libya, where assault and violence are increasingly recognized as a cause of facial injuries among Libya adults . Thus, it can be hypothesized that war and its related violence in Libya could have increased the risk of TDIs by increasing the antisocial behaviour and violent behaviour among children.…”
Section: Discussionmentioning
confidence: 99%
“…This could be the case for war-torn Libya, where assault and violence are increasingly recognized as a cause of facial injuries among Libya adults. 36 Thus, it can be hypothesized that war and its related violence in Libya could have increased the risk of TDIs by increasing the antisocial behaviour and violent behaviour among children. However, it is not known whether TDIs from assault and violence are increasing among Libyan children, although pre-conflict data suggested that violence was an uncommon cause of TDIs among Libyan children, accounting for 10% of injuries.…”
Section: Arheiam Et Almentioning
confidence: 99%